PENGARUH MULTIMEDIA PEMBELAJARAN INTERAKTIF TERHADAP HASIL BELAJAR DI SMP NEGERI 1 PATTALASSANG - Ummiana; Mustamin; Wahab, Abdul; Syahid, Akhmad; Azhar, Muh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of interactive learning multimedia on the learning outcomes of eighth-grade students in the Islamic Religious Education subject at SMP Negeri 1 Pattallassang, Gowa Regency. The study employs a quantitative method with an associative approach. The population consisted of 108 students, with a sample of 52 students determined using Slovin's formula via simple random sampling. Data collection was conducted using Likert-scale questionnaires and documentation. Research instruments were tested for validity using Pearson Product Moment correlation and for reliability using Cronbach’s Alpha. Data analysis involved descriptive and inferential statistics, including prerequisite tests (normality, linearity, and homogeneity), followed by simple linear regression analysis, the t-test, and the coefficient of determination (R²). The results indicate that interactive learning multimedia does not have a significant effect on student learning outcomes. This is evidenced by the t-test result, which yielded a t-value of -0.931 with a significance value of 0.357 (> 0.05); consequently, the null hypothesis (H₀) was accepted and the alternative hypothesis (Hₐ) was rejected. Furthermore, the coefficient of determination showed an R-value of 0.130 and an R² value of 0.017, meaning that interactive learning multimedia contributed only 1.7% to the variation in student learning outcomes, while 98.3% was influenced by factors outside the scope of this study. Thus, it can be concluded that interactive learning multimedia has not yet exerted a significant influence on the learning outcomes of eighth-grade students in Islamic Religious Education at SMP Negeri 1 Pattallassang, Gowa Regency. Nevertheless, interactive learning multimedia can still serve as a supporting learning tool when combined with appropriate teaching strategies, teacher readiness, and active student engagement.